مقاصد القرآن في إحياء قِيم الإنسان الحضارية - نور الدين مختار الخادمي (International Institute of Islamic Thought, 2017)
مقاصد القرآن الكريم هي أبعاده الغائية والمصحلية، وأسراره الحكمية التعليلية، وآفاقه في إقامة الحضارة وترشيد إنتاجها المادي والروحي لإسعاد الإنسان في الدنيا والآخرة وفق هدي القرآن. وقد حدد البحث أربعة مقاصد  تمثل أربع دوائر من القيم هي قيم حضارة الإنسان، وقيم الأصل الإنساني، وقيم الأسرة والبناء الاجتماعي، وقيم المحيط البيئي. The Intents of the Glorious Quran are its teleological and beneficial dimensions, its wise and explanatory mysteries, and its prospects in establishing civilization and rationalizing its material and spiritual production for the benefits of Man in this world and the hereafter within the guidance of the Qur'an. The paper identifies four intents that represent four areas of values: values of human civilization, values of human origin, values of family and social construction, and environmental values.